Generating synthetic data from administrative health records for drug safety and effectiveness studies - Olawale F. Ayilara; Robert W. Platt; Matt Dahl; Janie Coulombe; Pablo Gonzalez Ginestet; Dan Chateau; Lisa M. Lix (International Journal of Population Data Science, 2023)
Introduction Administrative health records (AHRs) are used to conduct population-based post-market drug safety and comparative effectiveness studies to inform healthcare decision making. However, the cost of data extraction, and the challenges associated with privacy and securing approvals can make it challenging for researchers to conduct methodological research in a timely manner using real data. Generating synthetic AHRs that reasonably represent the real-world data are beneficial for developing analytic methods and training analysts to rapidly implement study protocols. We generated synthetic AHRs using two methods and compared these synthetic AHRs to real-world AHRs. We described the challenges associated with using synthetic AHRs for real-world study.